Analisis Penerapan Metode Ceramah Plus Pada Mata Pelajaran Pendidikan Agama Islam di SMP Tunas Mandiri Kabupaten Langkat - Juleha, Juleha; Zuliana, Zuliana (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This thesis is a discussion that aims to find out 1. How is the application of the lecture plus method in learning Islamic religious education at Tunas Mandiri Junior High School, Langkat Regency. 2. What are the factors that hinder the process of applying the lecture plus method to learning Islamic religious education at SMP Tunas Mandiri, Langkat Regency. Sources of data in the study were school principals, teachers and students. The research instruments used were observation guidelines and interviews. The data analysis techniques used are data reduction, data presentation and data verification. The results of the research can be summarized as follows: 1) the application of the question and answer method, namely the teacher uses a learning design in the form of a question and answer method which is carried out during the evaluation to find out whether the students are able to answer and understand the lesson that has been given. The learning outcomes of Islamic religious education are: With the question and answer method, the teacher can find out the student learning outcomes themselves by preparing basic questions for students, so that students are confident and dare to answer any material submitted. and educational learning outcomes Islamic religion at Tunas Mandiri Middle School, which initially only had a few students who were active so that in the future it would increase again due to the pattern of teacher and principal implementation that was applied during the learning process. 2) The inhibiting factors for teachers in applying the question and answer method at Tunas Mandiri Middle School are: the learning process, namely the lack of understanding of students plus the limited time during the learning process.